Korean frailty and aging cohort study (KFACS): cohort profile - Chang Won Won; Sam-Gyu Lee; BeLong Cho; Hak Chul Jang; Hyeon Ju Kim; Jinhee Kim; Eun Roh; Kyung Mook Choi; Seoyoon Lee; Doukyoung Chon; Sunyoung Kim; Chang-O Kim; et al. (BMJ Open)
Purpose The purpose of the Korean Frailty and Aging Cohort Study (KFACS) is to initiate a nationwide, population-based prospective cohort study of older adults living in the community to assess their frailty status and explore transitions between frailty states over time in Korea.Participants The KFACS is a multicentre longitudinal study with the baseline survey conducted from May 2016 to November 2017. Each centre recruited participants using quota sampling stratified by age and sex. The number of participants recruited through 2 years of baseline study from 10 centres was 3014, with each site accounting for approximately 300 participants. The inclusion criteria were: having an age of 70–84 years, currently living in the community, having no plans to move out in the next 2 years, having no problems with communication and no prior dementia diagnosis.Findings to date To define physical frailty, the KFACS used a modified version of the Fried Frailty Phenotype (FFP) consisting of five components of frailty: unintended weight loss, weakness, self-reported exhaustion, slowness and low physical activity. In the baseline study of 2016–2017, 2907 of 3014 individuals fulfilled all five components of FFP. The results indicated that 7.8% of the participants (n=228) were frail, 47.0% (n=1366) were prefrail and 45.2% (n=1313) were robust. The prevalence of frailty increased with age in both sexes; in the group aged 70–74 years, 1.8% of men and 3.7% of women were frail, whereas in the 80–84 years age group, 14.9% of men and 16.7% of women were frail. Women tended to exhibit a higher prevalence of frailty than men in all age groups.Future plans The KFACS plans to identify outcomes and risk factors associated with frailty by conducting a 10-year cohort study, with a follow-up every 2 years, using 3014 baseline participants.